LaBr3(Ce) gamma-ray detector for neutron capture therapy. Issue 4 (January 2016) - Smirnova, M; Shmanin, E; Galavanov, A; Shustov, A; Ulin, S; Vlasik, K; Dmitrenko, V; Novikov, A; Orlov, A; Petrenko, D; Shmurak, S; Uteshev, Z
Abstract: Results of developing of a gamma-ray detector based on LaBr3 (Ce) scintillation crystal for neutron capture therapy are presented. An energy resolution of the detector measured by photomultiplier tube Hamamatsu R6233-100 is showed. It was 2.93% for gamma line 662 keV from a source 137 Cs. For radiative capture gamma line of isotope 10 B (478 keV) and annihilation line (511 keV) the values were 3.33 and 3.24% respectively. Data analysis of gamma spectra for an estimation of energy resolution threshold required for visual identification gamma lines 478 and 511 keV was made.